2004
DOI: 10.1590/s0004-282x2004000400002
|View full text |Cite
|
Sign up to set email alerts
|

Visual event-related potencial (P300): a normative study

Abstract: -The P300 component of the Event-Related Potential (ERP) is a general measurement of "cognitive efficiency". It is an index of the ability of an individual's Central Nervous System (CNS) to process incoming information. Objective: To develop a normative database for the visual P300. Methodology: 30 right-handed individuals (same number of each sex), between 20 and 30 years of age, healthy, free of any cognitive impairment and not making use of psychoactive substances. Participants were submitted to a visual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
(27 reference statements)
2
5
1
5
Order By: Relevance
“…The P300 latency increase is considered to be a delay in the information processing, translating the neu-ron transmission speed and the memory reload and alertness in the subjects [30]. Results from another research are also in agreement with the findings showed in the present study.…”
Section: Latencysupporting
confidence: 92%
See 1 more Smart Citation
“…The P300 latency increase is considered to be a delay in the information processing, translating the neu-ron transmission speed and the memory reload and alertness in the subjects [30]. Results from another research are also in agreement with the findings showed in the present study.…”
Section: Latencysupporting
confidence: 92%
“…Such modifications occur, due to the fact of this wave being easily influenced by specific parameters such as task, paradigm and stimulus [30].…”
Section: Amplitudementioning
confidence: 99%
“…Studies combining caffeine, bromazepam and P300 are practically inexistant in current literat u re . Thus, the present study aimed at investigating the distinct neuromodulatory effects of theses drugs on the visual ERP (P300), by comparing the results with a P300 normative database 24 .…”
Section: Snc) O B J E T I V Omentioning
confidence: 99%
“…P300 latans ve genliği bilişsel performans yeteneğini yansıtır. İşitsel ya da görsel uyaran ile oluşturula-bilirler (8). P300 potansiyellerinin multipl skleroz, inme, demans, Parkinson hastalığı, epilepsi, belirgin depresyon ve şizofreni gibi çeşitli nörolojik ve psikiyatrik hastalıklarda bilişsel değerlendirme için güveni-lir bir nörofizyolojik belirleyici olabileceği ileri sü-rülmüştür (9-15).…”
Section: Introductionunclassified